SYSTEMS ANALYSIS AND DESIGN OF GOODS INVENTORIES AND SALES IN. PROSPEROUS LANGGENG - Gunawan Gunawan; Eko Hadiyanto, SSI, MMSI (Jurnal Sistem Informasi, 2003)
There are several weaknesses that caused some of the procedures manual and createda lack of quality reports / very useful for accurate evaluation of their businessdevelopment. In other words the existing system not supporting the optimality of thecompany operations.Therefore, the authors make the analysis and design of new systems on the basis ofthe results of observations on the weaknesses of the old. With the hope of theproblems caused when using the system can be resolved and resolved or made aminimum.